The impact of social exclusion on experiential sports consumption: the chain mediating roles of loneliness and the need for social connection - Li, Chenya; Qu, Weihua (Frontiers in Psychology, 2025)
IntroductionWith the advancement of the social economy, sports consumption has shifted from traditional material-based purchases to experiential sports consumption, emphasizing psychological engagement and emotional fulfillment. However, the psychological mechanisms behind experiential sports consumption remain underexplored, especially in the context of social exclusion.MethodsThis study is grounded in social exclusion theory, constructing a conceptual model where social exclusion is the independent variable, experiential sports consumption intention is the dependent variable, and loneliness and the need for social connection serve as mediators. A survey was conducted with 415 valid responses, and data were analyzed using structural equation modeling and the Bootstrap method to examine the relationships among the variables.ResultsThe findings indicate that social exclusion significantly and positively predicts the intention to engage in experiential sports consumption. It also has a significant positive effect on loneliness and the need for social connection. However, loneliness does not mediate the relationship between social exclusion and experiential sports consumption intention, while the need for social connection does. Furthermore, a chain mediation effect exists between loneliness and the need for social connection in the relationship between social exclusion and experiential sports consumption intention.DiscussionThese results suggest that sports organizations and enterprises should design socially engaging activities that strengthen social connections and alleviate feelings of exclusion. This study enriches the theoretical understanding of social exclusion and its impact on experiential sports consumption, providing practical insights for enhancing social inclusion through sports.